Prevalence of Low Back Pain among Physiotherapy Students of Riphah College of Rehabilitation Sciences - Kashif, Muhammad; Kokab, Tasbeeh; Rafique, Zobia; Arshi, Aatik; Iram, Humaira (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To determine the prevalence of low back pain among physiotherapy students studying at Riphah College of Rehabilitation Sciences Faisalabad. Methodology: This cross-sectional study was conducted among 110 female students Riphah College of Rehabilitation Sciences (RCRS) during the academic year 2016–2017 from December 2016 to June 2017. The sample size for this study was calculated using Open Epi tool. Self- administered questionnaire was used and consisted of three sections; demographic information of the participants, the Standardized Nordic Musculoskeletal Questionnaire for the musculoskeletal complaints of low back and Visual Analogue Scale for pain intensity. The statistical analysis was performed with SPSS ver.18. Results: Out of 110 students, 61 (55.4%) had 12 months (prevalence period) Low back pain and 40 (36.4%) had a point prevalence (7 days prevalence). Of these 61 (55.4%) who had LBP, only 25 students stated that they were absent from university because of their back pain, and 32 (52.2%) of the participants thought that working activity during the last 12 months was affected by pain. Of 61 (55.5%) participants with back pain, 16 (26.7%) had mild, 23 (37.7%) had nagging, 19(31.1%) distressing, and 3 (4.9%) had severe pain. Conclusion: The prevalence of LBP in physiotherapy students is high and the most common type of pain is nagging in nature. Key words: Low back pain, prevalence, physiotherapy students, prolonged sitting